Out-of-plane buckling strength of free standing singly symmetric hollow pinned circular arches. (November 2021) - Rakici, Salih Can; Menkulasi, Fatmir
Abstract: This study deals with the out-of-plane flexural torsional buckling strength of singly symmetric free-standing circular arches with a hollow cross-section. The behavior of such arches is investigated numerically in terms of the out of plane critical elastic buckling load and ultimate load carrying capacity when such arches are subject to a radial pressure that creates uniform axial compression. Prediction methodologies proposed by other researchers for flexural torsional buckling of arches with an I-shaped cross-section, as well as American, European, and Australian code provisions for flexural buckling of compression members are slightly modified and compared with numerically obtained critical elastic buckling loads and ultimate load carrying capacities. All investigations are conducted using validated shell finite element simulations. A parametric study is conducted to evaluate the influence of arch depth, wall thickness, subtended angle, arch radius, yield strength, initial imperfections, and residual stresses on the 3D elastic-plastic behavior of such arches. It is concluded that it is not necessary to use eigenvalue buckling analysis to obtain critical elastic buckling loads for improving capacity predictions and that such loads may be obtained using existing formulations with slight modifications. Additionally, existing code provisions for flexural buckling of compression members may be used with minor modifications to predict the out-of-plane flexural torsional buckling capacity of such arches. Also, prediction methodologies proposed by other researchers for flexural torsional buckling of I-shaped arches may also be used with slight modifications and resulted in the most accurate, consistent, and design appropriate capacity predictions. Graphical abstract: Unlabelled Image Highlights: Various methods are presented to predict the out-of-plane buckling strength of FPCSH arches. Modifications to the presented methods are proposed to increase prediction accuracy. Proposed modifications pertain to the prediction of critical elastic buckling strength and consideration of imperfections. The accuracy of the proposed modifications is confirmed using validated FEA analysis. Eurocode provisions for arch bridges are determined to be inappropriate for FPCSH arches. A parametric study is conducted to understand the 3D elastic-plastic behavior of such arches.